Kemampuan Membaca dalam Hati Wacana Berbahasa Bali Siswa Kelas VIII.1 SMP Ngurah Rai Kerobokan, Kabupaten Badung - Kerianta, I Wayan (Dharma Sastra : Jurnal Penelitian Bahasa dan Sastra Daerah, 2024)
The research is conducted to achieve the following objectives: (1) to describe the silent reading ability of Balinese language texts by eighth-grade students (class VIII.1) at Ngurah Rai Kerobokan Junior High School, and (2) to describe the challenges faced by students when engaging in silent reading to comprehend the content of the text. This study aims to evaluate the reading comprehension ability of Balinese discourse among eighth-grade students (class VIII.1) at Ngurah Rai Kerobokan-Badung Junior High School. Data were collected and analyzed to determine the students' reading comprehension proficiency based on the assessment standards for Balinese language in eighth grade under the School-Based Curriculum (KTSP). The analysis revealed that the students' reading comprehension ability falls under the category of "less proficient," with an average score of 65. Despite the minimum passing grade (KKM) being set at 72, only 9 students (22.5%) were able to achieve it, while the remaining 31 students (77.5%) scored below the KKM. The main difficulties encountered by students in reading Balinese discourse include understanding vocabulary, language structure, and lack of interest in reading. Therefore, the majority of students are considered not proficient in reading Balinese discourse.